The Use of Mall (Mobile Assisted Language Learning) by Using Elsa (English Language Speech Assistant) Speak for Students’ Speaking Skills - Haliza, Haliza Putri Maharani; Yuri Lolita (Tadris Pendidikan Bahasa Inggris IAIN Langsa, 2024)
This study examined the responses of 7th-grade students at SMP Negeri 5 Sidoarjo to the ELSA Speak application and its impact on enhancing their English-speaking skills. The research aimed to evaluate student feedback on ELSA Speak and assess its influence on their language learning outcomes. A descriptive qualitative approach was utilized, incorporating closed-ended questionnaires and semi-structured interviews, based on the Technology Acceptance Model (TAM) to analyze technology adoption and usage. Despite the challenges, ELSA Speak significantly improved students' speaking skills. While there were technical issues related to the difference in access between free and premium versions, the overall positive impact on student engagement and proficiency highlighted ELSA Speak's potential as a valuable educational tool.